2013
DOI: 10.1152/ajprenal.00387.2012
|View full text |Cite
|
Sign up to set email alerts
|

Bardoxolone methyl analogs RTA 405 and dh404 are well tolerated and exhibit efficacy in rodent models of Type 2 diabetes and obesity

Abstract: Bardoxolone methyl and related triterpenoids are well tolerated and efficacious in numerous animal models potentially relevant to patients with Type 2 diabetes and chronic kidney disease. These agents enhance glucose control and regulate lipid accumulation in rodent models of diabetes and obesity, and improve renal function, reduce inflammation, and prevent structural injury in models of renal disease. However, a recent study in Zucker diabetic fatty (ZDF) rats noted poor tolerability with the bardoxolone meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
54
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 28 publications
4
54
1
Order By: Relevance
“…Differences in outcome between our study and that of Zoja et al (23) may reflect subtle disparity in drug dosage as well as differences in drug bioavailability between species. Our findings are, however, more in agreement with the study by Chin et al (24), in which it was shown that the BM analogs RTA 405 and dh404 were well tolerated in various rodent models of type 2 diabetes. Our study is also in agreement with the notion that activators of Nrf2 protect against diabetic nephropathy (9).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Differences in outcome between our study and that of Zoja et al (23) may reflect subtle disparity in drug dosage as well as differences in drug bioavailability between species. Our findings are, however, more in agreement with the study by Chin et al (24), in which it was shown that the BM analogs RTA 405 and dh404 were well tolerated in various rodent models of type 2 diabetes. Our study is also in agreement with the notion that activators of Nrf2 protect against diabetic nephropathy (9).…”
Section: Discussionsupporting
confidence: 93%
“…Livers were stained with hematoxylin and eosin and scored blinded on a scale of 0-5 to determine hepatocellular cytoplasmic rarification and periportal inflammation (24). Five to eight livers were examined per group.…”
Section: Histological Assessment Of Livermentioning
confidence: 99%
See 1 more Smart Citation
“…However, it was believed that impure compounds were responsible for the adverse effects in those studies [51]. Follow up studies demonstrated that using structural analogs lacking the impurities and at appropriate doses were unable to reproduce the adverse effects and that Dh404 is in fact well tolerated and exhibits efficacy in rodent models of T2DM [52]. It is believed these negative side effects were due to impure compounds and that Dh404 is both efficacious and well tolerated in several animal models and in humans.…”
Section: Targeting Keap1-nrf2 Dysregulationmentioning
confidence: 99%
“…Wu et al (2011) (Zoja et al, 2013). Despite this, rodent models examining kidney parameters continually showed efficacy of bardoxolone methyl and triterpenoid analogs (Reisman et al, 2012;Chin et al, 2013;Ding et al, 2013), giving reason to continue research into targeting the Nrf2 pathway. As previously mentioned, the Keap1-Nrf2 pathway is a highly conserved, ubiquitous response not only to stress, but also responsible for constitutive expression of genes regulated by ARE during basal conditions.…”
mentioning
confidence: 99%